Lithium battery negative electrode binder, preparation method and application

By synthesizing unsaturated carboxylic acid monomers containing carbamate bonds and urea bonds, a lithium battery negative electrode binder with high bonding effect and excellent cycle characteristics was prepared, which solved the problem of carboxylic embedding and emulsifiers affecting lithium ion migration in the prior art, and achieved more efficient battery performance.

CN119823673APending Publication Date: 2025-04-15WANHUA CHEM GRP CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411951176.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The negative electrode binder of the existing lithium battery causes carboxyl groups to be embedded during the polymerization process, affecting the bonding effect of the current collector, and small-molecular emulsifier affects the migration of lithium ions and reduces the cycling characteristics of the battery.

Method used

By synthesizing unsaturated carboxylic acid monomers containing carbamate bonds and urea bonds, the bonding effect of the adhesive is improved, and the unreacted monomers are removed by under-pressure distillation to prepare a binder with high solids content and suitable particle size.

Benefits of technology

It improves the bonding effect of the adhesive and the recycling performance of the battery, and enhances the high-temperature circulation characteristics and peeling performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005214910560000041
    Figure BDA0005214910560000041
  • Figure BDA0005214910560000051
    Figure BDA0005214910560000051
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a lithium battery negative electrode binder, and the preparation method comprises the following steps: 1) putting a polyisocyanate monomer and a hydroxyl-containing unsaturated monomer into a reaction kettle, fully and uniformly stirring, heating to 60-90 DEG C, and reacting for 4-6 hours; after the reaction is finished, adding an amino acid monomer, and continuously reacting for 5-8 hours to obtain an unsaturated carboxylic acid monomer containing a carbamate bond and a urea bond, which is marked as a component d; 2) putting all the carboxyl-free reaction monomers, unsaturated carboxylic acid monomers d containing carbamate bonds and urea bonds, an emulsifier, an initiator and water into a reaction kettle at one time, fully stirring, and heating to 50-80 DEG C to initiate polymerization; when the monomer is consumed to 90-98%, cooling to 30 DEG C and stopping the reaction; finally, unreacted monomers are removed in a reduced pressure distillation mode, and the binder is prepared. According to the method, an unsaturated carboxylic acid monomer containing a carbamate bond and a urea bond is synthesized, so that the bonding effect of the adhesive and the recycling performance of the battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a binder, and in particular to a lithium battery negative electrode binder and a preparation method and application thereof. Background Art

[0002] As portable terminals such as mobile phones have become more popular, they are being miniaturized, lightweighted, and have higher performance. In addition, lithium batteries are being required to be miniaturized, lightweighted, and have higher performance, just like the portable terminals.

[0003] In order to improve the performance of lithium batteries, the improvement of electrodes, electrolytes and other battery components has been studied. Among them, the electrode is manufactured by the following method: dispersing or dissolving a binder polymer in water or an organic solvent, and then mixing an electrode active material and a conductive agent such as conductive carbon into the formed liquid composition to obtain a slurry composition, and the slurry composition is applied to a collector and dried. Regarding electrodes, in addition to studying the electrode active material and the collector itself, the prior art also studies the binder and various additives used to bond the electrode active material to the collector.

[0004] Patent CN103782426B discloses a method for preparing a negative electrode binder for lithium batteries, which improves adhesion by introducing unsaturated carboxylic acid monomers. However, during the polymerization process, the unsaturated carboxylic acid monomers are more embedded in the particles due to the cross-linking effect of butadiene and cannot migrate to the surface, which has limited improvement on the bonding effect of the current collector.

[0005] Patent CN104471762A discloses a method for preparing a negative electrode binder for lithium batteries, which uses a small molecule ion emulsifier to improve the stability of the slurry. However, the small molecule emulsifier will affect the migration of lithium ions, thereby reducing the cycle characteristics of the battery. Summary of the invention

[0006] In view of the above technical problems, the present invention proposes a method for preparing a binder for lithium batteries. By synthesizing an unsaturated carboxylic acid monomer containing a carbamate bond and a urea bond, the bonding effect of the binder and the recycling performance of the battery can be improved.

[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0008] A process for preparing a binder comprises the following steps:

[0009] 1) Put polyisocyanate monomer and hydroxyl-containing unsaturated monomer into a reaction kettle, stir well, heat to 60-90°C, and react for 4-6 hours; after the reaction, add amino acid monomer, and continue to react for 5-8 hours to obtain unsaturated carboxylic acid monomer containing carbamate bond and urea bond, which is recorded as component d;

[0010] 2) All non-carboxyl reactive monomers, unsaturated carboxylic acid monomers d containing carbamate bonds and urea bonds, emulsifiers, initiators, and water are put into a reaction kettle at once, and after sufficient stirring, the temperature is raised to 50-80° C. to initiate polymerization; when the monomers are consumed to 90-98%, the temperature is lowered to 30° C. to stop the reaction; and finally, unreacted monomers are removed by reduced pressure distillation to obtain a binder.

[0011] In the present invention, in step 1), the polyisocyanate monomer a is one or a combination of toluene diisocyanate, isophorone diisocyanate, hexamethylene diisocyanate, cyclohexane dimethylene diisocyanate, and 4,4'-dicyclohexylmethane diisocyanate.

[0012] In the present invention, in step 1), the hydroxyl-containing unsaturated monomer b is one or a combination of pentaerythritol triacrylate, trimethylolpropane diacrylate, glycerol diacrylate, hydroxyethyl acrylate, and hydroxyethyl methacrylate.

[0013] In the present invention, in step 1), the amino acid monomer c is one or a combination of glycine, aspartic acid, glutamic acid, and alanine.

[0014] In the present invention, in step 1), the molar ratio of the polyisocyanate monomer, the hydroxyl-containing unsaturated monomer, and the amino acid monomer is 1:0.5:0.5-1:1.5:1.5.

[0015] In a preferred embodiment, the reaction monomers in step 2) include the following three components: e, f, and g:

[0016] e. one or more aromatic vinyl monomers; preferably, the aromatic vinyl monomer is one or a combination of styrene, methyl styrene, vinyl toluene, divinyl toluene;

[0017] f. One or more conjugated diene monomers; preferably, the conjugated diene monomers are 1,3-butadiene, isoprene, 2-methyl-1,3-butadiene, or a combination thereof;

[0018] g. One or more unsaturated carboxylic acid alkyl ester monomers; preferably, the unsaturated carboxylic acid alkyl ester monomer is one or a combination of methyl methacrylate, butyl acrylate, ethyl acrylate and methyl acrylate.

[0019] In a preferred embodiment, the emulsifier in step 2) is recorded as component h, and the component h is one or a combination of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, sodium oleate, sodium dodecyl diphenyl ether disulfonate.

[0020] In a preferred embodiment, the initiator in step 2) is recorded as component i; the initiator i is one or a combination of ammonium persulfate, potassium persulfate, tert-butyl hydroperoxide, and cumene hydroperoxide.

[0021] In a preferred embodiment, based on the solid mass in the binder, according to the total mass 100%, the amount of the component d) is 1 to 10 wt%, preferably 2 to 8 wt%; the amount of the component e) is 15 to 75 wt%, preferably 20 to 70 wt%; the amount of the component f) is 15 to 75 wt%, preferably 20 to 70 wt%; the amount of the component g) is 1 to 10 wt%, preferably 1 to 6 wt%; the amount of the component h) is 0.2 to 3 wt%, preferably 0.5 to 2.0 wt%; the amount of the component i) is 0.1 to 1 wt%, preferably 0.2 to 0.8 wt%.

[0022] In a preferred embodiment, in step 2), the amount of water added is 0.5 to 3.0 times the total mass of solids in the binder.

[0023] In a preferred embodiment, in step 2), the reduced pressure distillation conditions are a temperature of 50-60° C. and a negative pressure of 70-90 KPa for distillation for 2-4 hours.

[0024] On the other hand, the present invention provides a binder prepared by the above process, wherein the solid content of the binder is not less than 20%, preferably 30-50wt%, and the particle size is 60-400nm.

[0025] Finally, the present invention provides an application of the binder in a lithium battery.

[0026] The preparation process of the binder provided by the present invention has the following advantages:

[0027] By using an unsaturated carboxylic acid monomer containing a carbamate bond and a urea bond, the bonding effect of the adhesive and the recycling performance of the battery can be improved: a) The unsaturated carboxylic acid monomer with a long-chain side group can avoid the carboxyl group being embedded inside the particle during the polymerization process; b) The carbamate bond has good flexibility and can increase the cycle life of the battery; c) The urea bond is adjacent to the carboxyl group, and the bonding performance of the carboxyl group and the current collector is improved by increasing the hydrogen bond density. DETAILED DESCRIPTION

[0028] The present invention is further described below by means of specific examples. The examples described in the present invention are only used to illustrate the present invention and do not limit the scope of the present invention.

[0029] Some specific steps in the experimental methods used in the following examples are routine operations unless otherwise specified.

[0030] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0031] The main raw material information is as follows:

[0032] Table 1 Raw material information

[0033]

[0034]

[0035] Main performance test methods:

[0036] (1) Adhesion test with copper foil

[0037] The negative electrode of the battery made with a binder is cut into a rectangle with a length of 100 mm and a width of 10 mm as a test sample. For this sample, the surface of the negative electrode active material layer is facing downward, and a cellophane tape is attached to the surface of the negative electrode active material layer. The cellophane tape is fixed on a horizontal test bench. During the measurement, one end of the collector is stretched vertically upward at a tensile speed of 50 mm / min and peeled off. The measurement is performed 3 times, and the average value is calculated, and the average value is set as the peel strength (N / m).

[0038] (2) High temperature cycle characteristics

[0039] The battery made with the binder was left to stand at 25°C for 24 hours. The charge and discharge operation was performed by the constant current method of 0.1C, charging to 4.2V and discharging to 3.0V, and the capacity (initial capacity C0) at this time was measured; at 60°C, the charge and discharge operation was repeated 100 times by the constant current method of 0.1C, charging to 4.2V and discharging to 3.0V, and the capacity C1 after 100 charge and discharge operations was measured. The high-temperature cycle characteristics were evaluated by expressing the capacity change rate as △C=C1 / C0×100(%). The higher the capacity change rate, the better the high-temperature cycle characteristics.

[0040] Example 1

[0041] 2.54 g of TDI and 4.36 g of pentaerythritol triacrylate were added to a reaction kettle, fully stirred, and then heated to 60°C. After reacting for 4 h, 1.10 g of glycine was added and the reaction was continued for 8 h to obtain 8.0 g of an unsaturated carboxylic acid monomer containing a carbamate bond and a urea bond;

[0042] 20g butadiene, 70g styrene, 1.0g methyl methacrylate, 8.0g unsaturated carboxylic acid monomer containing carbamate bond and urea bond, 0.2g ammonium persulfate, 148g water, 0.5g sodium dodecyl sulfate were put into a pressure-resistant reactor with stirring at one time, and after sufficient stirring, the temperature was raised to 50°C to initiate polymerization. The monomer consumption was 90% through the solid content test, and the reaction was stopped by cooling to 30°C. The obtained emulsion was maintained at a temperature of 50°C and a negative pressure of 70Kpa, and vacuumed for 2h to remove the unreacted monomer by reduced pressure distillation, and the binder was finally obtained. The solid content of the emulsion was measured to be 40.0%, and the particle size was 100nm.

[0043] Example 2

[0044] 2.44 g IPDI and 2.09 g trimethylolpropane diacrylate were added to a reaction kettle, stirred thoroughly, and then heated to 70°C. After reacting for 5 h, 1.46 g aspartic acid was added and the reaction was continued for 7 h to obtain 6.0 g of an unsaturated carboxylic acid monomer containing a carbamate bond and a urea bond.

[0045] 30g butadiene, 60g styrene, 2.0g isooctyl acrylate, 6.0g unsaturated carboxylic acid monomer containing carbamate bond and urea bond, 0.3g potassium persulfate, 98g water, 1.0g sodium dodecyl sulfate were put into a pressure-resistant reactor with stirring at one time, and after sufficient stirring, the temperature was raised to 55°C to initiate polymerization. When the monomer was consumed to 92%, the temperature was lowered to 30°C to stop the reaction. The obtained emulsion was maintained at a temperature of 60°C and a negative pressure of 70Kpa, and vacuumed for 2h to remove the unreacted monomer by reduced pressure distillation, and the adhesive was finally obtained. The solid content of the emulsion was 50.0% and the particle size was 120nm.

[0046] Example 3

[0047] 1.40 g HDI and 2.38 g glycerol diacrylate were added to a reaction kettle, stirred thoroughly, and then heated to 80°C. After reacting for 6 h, 1.23 g glutamic acid was added and the reaction was continued for 6 h to obtain 5.0 g of an unsaturated carboxylic acid monomer containing a carbamate bond and a urea bond.

[0048] 40g butadiene, 50g styrene, 3.0g butyl acrylate, 5.0g unsaturated carboxylic acid monomer containing carbamate bond and urea bond, 0.4g ammonium persulfate, 230g water, 1.5g sodium dodecyl sulfate were put into a pressure-resistant reactor with stirring at one time, and after sufficient stirring, the temperature was raised to 60°C to initiate polymerization. When the monomer was consumed to 94%, the temperature was lowered to 30°C to stop the reaction. The obtained emulsion was kept at a temperature of 50°C and a negative pressure of 90Kpa, and vacuumed for 2h to remove the unreacted monomer by reduced pressure distillation, and the adhesive was finally obtained. The solid content of the emulsion was 30.0% and the particle size was 140nm.

[0049] Example 4

[0050] 2.24 g HMDI and 0.99 g hydroxyethyl acrylate were added to a reaction kettle, stirred thoroughly, and then heated to 75°C. After reacting for 5.5 h, 0.76 g alanine was added and the reaction was continued for 5 h to obtain 4.0 g of an unsaturated carboxylic acid monomer containing a carbamate bond and a urea bond.

[0051] 50g butadiene, 40g styrene, 4.0g methyl methacrylate, 4.0g unsaturated carboxylic acid monomer containing carbamate bond and urea bond, 0.5g ammonium persulfate, 183g water, 2.0g sodium dodecyl sulfate were put into a pressure-resistant reactor with stirring at one time, and after sufficient stirring, the temperature was raised to 65°C to initiate polymerization. When the monomer was consumed to 96%, the temperature was lowered to 30°C to stop the reaction. The obtained emulsion was maintained at a temperature of 50°C and a negative pressure of 70Kpa, and vacuumed for 4h to remove the unreacted monomer by reduced pressure distillation, and the binder was finally obtained. The solid content of the emulsion was 35% and the particle size was 160nm.

[0052] Example 5

[0053] 1.33g TDI and 0.99g hydroxyethyl methacrylate were added into a reaction kettle, stirred thoroughly, and then heated to 65°C. After reacting for 4.5h, 0.68g alanine was added and the reaction was continued for 5.5h to obtain 3.0g of an unsaturated carboxylic acid monomer containing a carbamate bond and a urea bond.

[0054] 60g butadiene, 30g styrene, 5.0g methyl methacrylate, 3.0g unsaturated carboxylic acid monomer containing carbamate bond and urea bond, 0.6g potassium persulfate, 120g water, 0.8g sodium dodecyl sulfate were put into a pressure-resistant reactor with stirring at one time, and after sufficient stirring, the temperature was raised to 70°C to initiate polymerization. When the monomer was consumed to 98%, the temperature was lowered to 30°C to stop the reaction. The obtained emulsion was maintained at a temperature of 55°C and a negative pressure of 80Kpa, and vacuumed for 2h to remove the unreacted monomer by reduced pressure distillation, and the binder was finally obtained. The solid content of the emulsion was 45% and the particle size was 160nm.

[0055] Example 6

[0056] 0.67 g IPDI and 0.89 g pentaerythritol triacrylate were added to a reaction kettle, stirred thoroughly, and then heated to 65°C. After reacting for 4.5 h, 0.44 g glutamic acid was added and the reaction was continued for 5.5 h to obtain 2.0 g of an unsaturated carboxylic acid monomer containing a carbamate bond and a urea bond.

[0057] 70g butadiene, 20g styrene, 6.0g butyl acrylate, 2.0g unsaturated carboxylic acid monomer containing carbamate bond and urea bond, 0.8g potassium persulfate, 148g water, 1.6g sodium dodecyl sulfate were put into a pressure-resistant reactor with stirring at one time, and after sufficient stirring, the temperature was raised to 80°C to initiate polymerization. When the monomer was consumed to 98%, the temperature was lowered to 30°C to stop the reaction. The obtained emulsion was maintained at a temperature of 60°C and a negative pressure of 90Kpa, and vacuumed for 3h to remove the unreacted monomer by reduced pressure distillation, and the adhesive was finally obtained. The solid content of the emulsion was 40% and the particle size was 180nm.

[0058] Comparative Example 1

[0059] 20g butadiene, 70g styrene, 1.0g methyl methacrylate, 8.0g methacrylic acid, 0.2g ammonium persulfate, 148g water, and 0.5g sodium dodecyl sulfate were put into a pressure-resistant reactor with stirring at one time. After sufficient stirring, the temperature was raised to 50°C to initiate polymerization. When the monomers were consumed to 90%, the temperature was lowered to 30°C to stop the reaction. The obtained emulsion was maintained at a temperature of 50°C and a negative pressure of 70Kpa, and vacuumed for 2h to remove the unreacted monomers by reduced pressure distillation. Finally, the binder was obtained, and the solid content of the emulsion was 40.0% and the particle size was 100nm.

[0060] Comparative Example 2

[0061] 20g butadiene, 70g styrene, 1.0g methyl methacrylate, 8.0g itaconic acid, 0.2g ammonium persulfate, 148g water, and 0.5g sodium dodecyl sulfate were put into a pressure-resistant reactor with stirring at one time. After sufficient stirring, the temperature was raised to 50°C to initiate polymerization. When the monomers were consumed to 90%, the temperature was lowered to 30°C to stop the reaction. The obtained emulsion was maintained at a temperature of 50°C and a negative pressure of 70Kpa, and vacuumed for 2h to remove the unreacted monomers by reduced pressure distillation. Finally, the binder was obtained, and the solid content of the emulsion was measured to be 40.0%, and the particle size was 100nm.

[0062] Application performance testing:

[0063] The SBR polymer latex prepared in each embodiment and comparative example was tested for adhesion and high temperature cycle characteristics. The results are shown in Table 1:

[0064] Table 1. Performance test results

[0065] Adhesion High temperature cycle characteristics Example 1 15.5N / m 85% Example 2 16.4N / m 86% Example 3 17.1N / m 86% Example 4 14.8N / m 88% Example 5 16.5N / m 90% Comparative Example 1 8.1N / m 57% Comparative Example 2 7.3N / m 52%

[0066] It can be seen from the test results of the SBR polymer latex prepared in the above embodiments and comparative examples that the binder prepared by the present invention can improve the cycle characteristics of lithium batteries while maintaining high stripping performance in the field of lithium batteries, thereby enabling it to have a wider range of applications and significant competitive advantages in the field of lithium batteries.

[0067] The above is only a preferred embodiment of the present invention. It should be pointed out that ordinary technicians in this field can make several improvements and supplements without departing from the method of the present invention. These improvements and supplements should also be regarded as the scope of protection of the present invention.

Claims

1. A process for preparing a binder, comprising the following steps: 1) Put polyisocyanate monomer and hydroxyl-containing unsaturated monomer into a reaction kettle, stir well, heat to 60-90°C, and react for 4-6 hours; after the reaction, add amino acid monomer, and continue to react for 5-8 hours to obtain unsaturated carboxylic acid monomer containing carbamate bond and urea bond, which is recorded as component d; 2) All non-carboxyl reactive monomers, unsaturated carboxylic acid monomers d containing carbamate bonds and urea bonds, emulsifiers, initiators, and water are put into a reaction kettle at once, and after sufficient stirring, the temperature is raised to 50-80° C. to initiate polymerization; when the monomers are consumed to 90-98%, the temperature is lowered to 30° C. to stop the reaction; and finally, unreacted monomers are removed by reduced pressure distillation to obtain a binder.

2. The preparation process according to claim 1, characterized in that: In step 1), the polyisocyanate monomer a is one or a combination of toluene diisocyanate, isophorone diisocyanate, hexamethylene diisocyanate, cyclohexane dimethylene diisocyanate, and 4,4'-dicyclohexylmethane diisocyanate.

3. The preparation process according to claim 1 or 2, characterized in that: In step 1), the hydroxyl-containing unsaturated monomer b is one or a combination of pentaerythritol triacrylate, trimethylolpropane diacrylate, glycerol diacrylate, hydroxyethyl acrylate, and hydroxyethyl methacrylate.

4. The preparation process according to any one of claims 1 to 3, characterized in that: In step 1), the amino acid monomer c is one or a combination of glycine, aspartic acid, glutamic acid, and alanine; and / or, in step 1), the molar ratio of the polyisocyanate monomer, the hydroxyl-containing unsaturated monomer, and the amino acid monomer is 1:0.5:0.5-1:1.5:1.

5.

5. The preparation process according to any one of claims 1 to 4, characterized in that: In step 2), the reaction monomers include the following three components: e, f, and g: e. one or more aromatic vinyl monomers; preferably, the aromatic vinyl monomer is one or a combination of styrene, methyl styrene, vinyl toluene, divinyl toluene; f. One or more conjugated diene monomers; preferably, the conjugated diene monomers are 1,3-butadiene, isoprene, 2-methyl-1,3-butadiene, or a combination thereof; g. One or more unsaturated carboxylic acid alkyl ester monomers; preferably, the unsaturated carboxylic acid alkyl ester monomer is one or a combination of methyl methacrylate, butyl acrylate, ethyl acrylate and methyl acrylate.

6. The preparation process according to any one of claims 1 to 5, characterized in that: In step 2), the emulsifier is recorded as component h, and the component h is one or a combination of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, sodium oleate, and sodium dodecyl diphenyl ether disulfonate; and / or, the initiator in step 2) is recorded as component i; the initiator i is one or a combination of ammonium persulfate, potassium persulfate, tert-butyl hydroperoxide, and isopropylbenzene hydroperoxide.

7. The preparation process according to any one of claims 1 to 6, characterized in that: Based on the solid mass in the binder, according to the total mass 100%, the amount of the component d) is 1-10wt%, preferably 2-8wt%; the amount of the component e) is 15-75wt%, preferably 20-70wt%; the amount of the component f) is 15-75wt%, preferably 20-70wt%; the amount of the component g) is 1-10wt%, preferably 1-6wt%; the amount of the component h) is 0.2-3wt%, preferably 0.5-2.0wt%; the amount of the component i) is 0.1-1wt%, preferably 0.2-0.8wt%.

8. The preparation process according to any one of claims 1 to 7, characterized in that: In step 2), the amount of water added is 0.5 to 3.0 times the total mass of solids in the binder; and / or, the reduced pressure distillation conditions are a temperature of 50 to 60° C. and a negative pressure of 70 to 90 KPa for distillation for 2 to 4 hours.

9. The binder prepared by the preparation process according to any one of claims 1 to 8, wherein the solid content of the binder is not less than 20%, preferably 30 to 50 wt%, and the particle size is 60 to 400 nm.

10. Use of the binder prepared by the preparation process according to any one of claims 1 to 8 or the binder according to claim 9 in a lithium battery.

Citation Information

Patent Citations

  • Adhesive composition for negative electrode of secondary battery, negative electrode for secondary battery, slurry composition for negative electrode, manufacturing method and secondary battery

    CN103782426B

  • Slurry for lithium ion secondary battery negative electrodes, electrode for lithium ion secondary batteries, method for producing electrode for lithium ion secondary batteries, and lithium ion secondary battery

    CN104471762A